First responders’ occupational injury and disease associated with periods of extreme bushfires - Janneke Berecki-Gisolf; Win Wah; Malcolm R Sim; Deborah C Glass; Ryan F Hoy; Tim Driscoll; Alex Collie; Karen Walker-Bone (Scientific Reports, 2024)
Abstract There has been limited research on the health impacts of extreme bushfire exposure among emergency responders (ER) involved in suppressing extreme bushfires. This study aimed to evaluate the associations between extreme bushfires and ER’s compensated injury and illness in Victoria, Australia. State-wide ER compensation claims from January 2005 to April 2023 were analysed. Logistic regression modelling was used to identify factors associated with compensation claims during the extreme bushfire periods in 2009 and 2019/20, compared to all other claims, adjusting for seasonality (summer). Of the 44,164 included claims, 1105 (2.5%) had recorded injury/disease onset dates within extreme bushfire periods, and 11,642 (26.4%) occurred in summer months. Over half of claims were made by police (52.4%), followed by ambulance officers/paramedics (27.2%) and firefighters (20.5%). Extreme bushfire period claims were associated with older workers (odds ratio/OR = 1.58,95%CI = 1.30–1.92, ages ≥ 55 vs. 35–44 years). Mental disorders (OR = 1.61,95%CI = 1.25–2.07), intracranial injuries (OR = 3.04,95%CI = 1.69–5.48) and infections/parasites (OR = 3.11,95%CI = 1.61–5.98) vs. wounds were associated with extreme bushfire period claims. Given the expected increase in extreme bushfire events and the ageing workforce, study findings underscore the importance of primary and secondary prevention in ER. This can include periodic health surveillance for older workers, access to early treatment, and ongoing support for mental health conditions.